NETRALITAS NOTARIS SEBAGAI ANGGOTA LEGISLATIF: Studi Tentang Peran Notaris Cuti Sebagai Anggota Legislatif Terhadap Notaris Pengganti Terhadap Akta-akta Yang Dibuatnya - Nur Cahyaningsih; Akhmad Khisni (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2017)
The Regional People's Legislative Assembly, hereinafter referred to as the Regional People's Legislative Assembly (DPRD), is a representative institution of the regional people as an element of local government administration Legally and politically the DPRD has a strategic position in implementing development policies in the regions. The magnitude of the roles, functions and authorities of the legislature invites many elements of society to enter as members of the council, notary positions and many Land Acquisition Authorities who are left behind to follow the legislative election procession. As a first step, a notary and enter into the party membership, and follow all the procedures of scaling, to then be elected by the community to become members of the council. Notaries in exercising their right to sit on behalf of the community as members of the Council, also regulated in Law No. 7 of 2017 on General Elections, are said to have made a statement willing not to practice as notaries and officials of the land deed (hereinafter referred to as PPAT). From this it can lead to issues of provisions contained in Articles 3 and 17, namely dual positions. This study aims to determine the relationship of notary to leave with a substitute notary in the perspective of Law Number 30 Year 2004 regarding Position Notary. Article explaining, among other things, article 33, on this matter Notary, a Notary substitute has the same authority related to the making of authentic deeds made. The research approach used is normative juridical, which will be qualitatively analyzed normative against secondary data. The theory used by the author is the theory of authority, theory of responsibility and theoretical justice. If you look at the explanation and analyze from the articles of article regarding the Notary Substitute, the Article which explains, among others, article 33, regarding this Notary, the Notary substitute has the same authority regarding the making of authentic deeds made. The authority of notary and substitute notary is based on Article 15 of Law Number 2 Year 2014 concerning Notary Position. The authority of a substitute notary commences from the grant of a notary protocol until the expiry of the appointment period based on the decision of the Notary Supervisory Board. Procedures concerning notary leave with a substitute notary may result in a conflict of interest that may affect the independence of a notary who is not allowed to take sides, this is due to 2 (two) factors namely the rules themselves and the political factor. Procedures concerning notary leave with a substitute notary may result in a conflict of interest that may affect the independence of a notary who is not allowed to take sides, this is due to 2 (two) factors namely the rules themselves and the political factor. The solution is to reinforce the terms of nomination of legeslative members, not just to not practice (leave) but with the resignation as a notary or PPAT and release all attributes (nameplate, practice office, and so on).Keywords: Notary, Authority, Conflict of Interest, Legislative Member